2015
DOI: 10.32007/med.1936/jfacmedbagdad.v57i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Serum Adiponectin Levels in Normal Weight Women with Polycystic Ovary Syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age with primary manifestations of infertility, menstrual dysfunction and clinical or biochemical hyperandrogenism (hirsutism, acne and elevated androgen). Adiponectin is the most abundant adipokine. It has insulin-sensitizing, anti-atherogenic, and antiinflammatory actions. Objective: Low adiponectin levels in women with PCOS have been largely attributed to obesity which is common among these patients. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…Also, impairment in FSH secretion lead to an elevation in LH/FSH ratio in PCOS patients (14). In addition, the data of this study demonstrated that higher levels of fasting serum glucose, insulin, and HOMA-IR in PCOS group when compared with controls group which agree with previous studies (15,16,17,18). Hyperinsulinemia, peripheral insulin resistance, and impaired glucose tolerance are principle metabolic abnormalities seen in PCOS (19).…”
Section: Discussionsupporting
confidence: 91%
“…Also, impairment in FSH secretion lead to an elevation in LH/FSH ratio in PCOS patients (14). In addition, the data of this study demonstrated that higher levels of fasting serum glucose, insulin, and HOMA-IR in PCOS group when compared with controls group which agree with previous studies (15,16,17,18). Hyperinsulinemia, peripheral insulin resistance, and impaired glucose tolerance are principle metabolic abnormalities seen in PCOS (19).…”
Section: Discussionsupporting
confidence: 91%